Penyuluhan Rumah Layak Huni dan Pengetahuan Usaha Mikro Kecil Menengah di Desa Kepau Jaya - Setiawan, Beny; Putra, Agus Alisa; Muhammad, Adam (Journal of Social and Community Service, 2024)
This Community Service activity was carried out in Kepau Jaya Village, Siak Hulu District, Kampar Regency, with a focus on providing education on livable housing and increasing knowledge of Micro, Small, and Medium Enterprises (MSMEs). The program's objective was to raise public awareness of the importance of housing that meets health and comfort standards, while also providing education on managing and developing small-scale businesses. Implementation methods included outreach, training, interactive discussions, and hands-on practice involving local residents, village officials, and MSMEs. The results of the activity showed an increase in public understanding of the concept of livable housing, including aspects of sanitation and spatial planning, as well as increased insight and skills of business actors in marketing strategies, product innovation, and simple financial management. This program contributed to community empowerment, encouraged local economic independence, and strengthened the relationship between universities and the community through the transfer of applicable knowledge.